Quality control - Besterfield, Dale H. (New Jersey Pearson Education, 2009)
This book provides fundamental-yet comprehensive-coverage of quality control concepts. Sufficient theory is presented to ensure that readers gain a sound understanding of the basic principles of quality control. The substantial use of probability and statistical techniques is reduced to simple mathematics or is developed in the form of tables and charts.
Includes bibliography and index
Keywords: Quản trị kinh doanh